Reversal of anxiety-like depression induced by chronic corticosterone by crocin I and surface-enhanced Raman spectroscopy monitoring of plasma metabolites - Zhang, Dandan; Wu, Zhuodi; Yang, Doudou; Zhao, Guanjie; Zhang, Yanru; Mou, Weifeng; Liang, Yinku (Frontiers in Pharmacology, 2025)
Anxiety disorders and depression often co-occur and lack broadly available treatments. Gardenia extract significantly associated with treatment of anxiety-like depression. Based on the dose effect hypothesis and previous studies, it is speculated that crocin I, the main component of gardenia, is significantly related to the treatment of anxiety-like depression. The present study aimed to verify the reversal effect of crocin I on chronic corticosterone-induced anxiety-like depression, and to further explore its metabolic process in vivo. Ultimately, a new method for rapid and sensitive detection of trace substances was established. In this study, the rat model of anxiety-like depression was induced by chronic corticosterone. The effects of crocin I were explored by combining behavioral, pathological sections and ELASA data. It is the first time that crocin I can reverse the morphological changes of hippocampus induced by corticosterone in rats. In terms of behavior, crocin Ⅰ can significantly improve the anxiety-like depressive behavior exhibited by model rats in water maze and sugar water preference experiments. It can also repair neuronal cell damage in the Dentate gyrus, CA1, and CA3 areas of the hippocampus. It also regulates the expression levels of monoamine neurotransmitters in the rat brain, thereby exerting an anti-anxiety-like depression effect. Pharmacokinetic analysis was performed to determine the metabolic process in vivo. Further integrating Surface-Enhanced Raman Scattering (SERS) technology, a highly sensitive and rapid detection method for trace substances had been established. It was first discovered that crocin I can reverse the changes in rat hippocampal morphology caused by corticosterone. It was determined that crocin Ⅰ can reverse the anxiety-like depression induced by chronic corticosterone and exert its therapeutic effect by regulating the levels of neurotransmitters in the brain. In vivo pharmacokinetic experiments revealed that crocin Ⅰ could not pass through the intestinal barrier into the blood, but its metabolite crocetin could pass through the intestinal barrier into the blood. Finally, by synthesizing silver nanoparticles, a detection method for trace amounts of the metabolite crocetin in blood samples was established for the first time.The calculated enhancement factor is 4.49 × 1011. The method was stable and reproducible over a week. This series of studies revealed the great potential of crocin I in treating comorbid anxiety and depression. It shortens the distance from theoretical research to clinical application.